Integral Analysis of Field Work and Laboratory Electrical Resistivity Imaging for Saline Water Intrusion Prediction in Groundwater - Zawawi M.H.; Zahar M.F.; Hashim M.M.M.; Hazreek Z.A.M.; Zahari N.M.; Kamaruddin M.A. (Institute of Physics Publishing, 2023)
Aquifers; Boreholes; Climate change; Coastal zones; Electric conductivity; Groundwater geochemistry; Health hazards; Hydrogeology; Nondestructive examination; Potable water; Sea level; Seawater; Water supply; Conventional methods; Electrical resistivity imaging; Freshwater aquifer; Groundwater monitoring; Integrated approach; Non-destructive test; Observation wells; Saline water intrusion; Groundwater resources